Stereoselective Fluorescence Quenching in the Electron Transfer Photooxidation of Nucleobase-Related Azetidines by Cyanoaromatics - Ana B. Fraga-Timiraos; Gemma M. Rodríguez-Muñiz; Vicente Peiro-Penalba; Miguel A. Miranda; Virginie Lhiaubet-Vallet (Molecules, 2016)
Electron transfer involving nucleic acids and their derivatives is an important field in bioorganic chemistry, specifically in connection with its role in the photo-driven DNA damage and repair. Four-membered ring heterocyclic oxetanes and azetidines have been claimed to be the intermediates involved in the repair of DNA (6-4) photoproduct by photolyase. In this context, we examine here the redox properties of the two azetidine isomers obtained from photocycloaddition between 6-aza-1,3-dimethyluracil and cyclohexene. Steady-state and time-resolved fluorescence experiments using a series of photoreductants and photooxidants have been run to evaluate the efficiency of the electron transfer process. Analysis of the obtained quenching kinetics shows that the azetidine compounds can act as electron donors. Additionally, it appears that the cis isomer is more easily oxidized than its trans counterpart. This result is in agreement with electrochemical studies performed on both azetidine derivatives.